La crónica modernista centroamericana y sus posibilidades editoriales: tres obras que merecen una edición crítica. - Carvajal Muñoz, Osvaldo (2017)
This article formulates questions on one aspect of the modernist chronicle: its compilation and publishing in critical editions. An analysis is made of the case of three books by Latin American authors which were originally published in periodical editions: La vida de Rubén Darío Escrita por él mismo (1915) by Rubén Darío; Sensaciones de París y de Madrid (1900) by Enrique Gómez Carrillo; and El libro del trópico (1907) by Arturo Ambrogi. These works present particularities that constitute them as different models of the same philological problem. Therefore, they provide evidence of the benefits that the access to an annotated, critical edition of a text may offer to a contemporary reader’s reading process.